(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
Soluble dietary fibers of Trigonella foenum graecum Linn. seed were isolated and fractionatedinto neutral and acidic parts. Structures of both the fractions were determined by sugar analysis andhigh resolution 2D NMR spectroscopic studies including total correlation (TOCSY) spectroscopy.Main chain of the neutral SDF fraction was found to be a galactomannan composed of mannoseand galactose ( 1 : 1.5 ratio) having 1,3-? linkages between each other. Terminal mannose residuewas linked to galactose residue of the main chain at its 4 position by ?-linkage. The acidic SDF wasa rhamnogalacturonan, in the main chain, galacturonic acids and rhamnose had 1,4-?- and 1,2-?-linkeages, respectively. Terminal ?-galactose and ?-glucuronic acid were linked to ?-galacturonicacid of the main chain at its 3-position DOI: http://dx.doi.org/10.3329/jbas.v38i1.20201 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 1, 19-26, 2014